Close Reading in the Urban Classroom: A Teacher's Introspection - Sharonica Nelson (Networks: An Online Journal for Teacher Research, 2019)
The purpose of this action piece is to discuss my experience with teaching close reading in the urban classroom. It explains ideas and challenges that I encountered when teaching close reading in conjunction with close reading strategies. I detail close reading strategies and explain how they can be used advantageously. The article closes with ideas on how I learned the importance of promoting student self-application of strategies, incorporating strategies so that they are not time consuming, differentiating strategies, and ultimately, the idea of promoting reading for enjoyment.
Keywords: close reading; close reading strategies; literacy; love of reading; urban education